2015
DOI: 10.1039/c5ra09729k
|View full text |Cite
|
Sign up to set email alerts
|

Highly permeable ionic liquid membrane by both facilitated transport and the increase of diffusivity through porous materials

Abstract: BMIM BF4/Cu nanoparticles/KIT-6 composite membrane for facilitating CO2 transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For example, the addition of Cu nanoparticles to ILs caused their surface to become positively polarized and resulted in increased CO 2 permeance and selectivity [ 72 ]. Different ILs, such as [HMIM][NO 3 ], [OMIM][BF 4 ] or [BMIM][NO 3 ], have been tested with PES supports [ 73 , 74 ] and [BMIM][BF 4 ] with KIT-6 silica support [ 75 ]. The factors that affect the performance of this type of SILMs with Cu nanoparticles have been deeply investigated [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the addition of Cu nanoparticles to ILs caused their surface to become positively polarized and resulted in increased CO 2 permeance and selectivity [ 72 ]. Different ILs, such as [HMIM][NO 3 ], [OMIM][BF 4 ] or [BMIM][NO 3 ], have been tested with PES supports [ 73 , 74 ] and [BMIM][BF 4 ] with KIT-6 silica support [ 75 ]. The factors that affect the performance of this type of SILMs with Cu nanoparticles have been deeply investigated [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gas separation performances of IL-based composite membranes can be improved by increasing IL contents, but the high-content IL will decrease the mechanical property of the membranes. Adding some inorganic particles or MOFs with better gas separation performances, including SAPO-34, , ZIF-8, , and others, is a promising strategy to make membrane simultaneously possess high separation performances and great long-term stability. Hudiono et al , reported a novel MMM containing three components, a styrene-based poly­(IL), an IL ([Emim]­[Tf 2 N]) and SAPO-34 zeolite particles for CO 2 separation.…”
Section: Structure Effectsmentioning
confidence: 99%
“…(d) Permeance of CO 2 and CH 4 through MoS 2 SILM-3 at a pressure of 0.06 MPa at room temperature for 7 days. The separation performances of MoS 2 SILMs compared with other supported [Bmim]­[BF 4 ] membranes (black squares): (e) CO 2 /N 2 and (f) CO 2 /CH 4 , respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Compared with neat [BMIM]­[BF 4 ], MoS 2 SILMs show excellent selectivity for gases. We attribute it to nanoconfined [BMIM]­[BF 4 ] in the nanochannels.…”
Section: Results and Discussionmentioning
confidence: 99%